2020
DOI: 10.1038/s41598-020-72750-9
|View full text |Cite
|
Sign up to set email alerts
|

Cell type specific gene expression profiling reveals a role for complement component C3 in neutrophil responses to tissue damage

Abstract: Tissue damage induces rapid recruitment of leukocytes and changes in the transcriptional landscape that influence wound healing. However, the cell-type specific transcriptional changes that influence leukocyte function and tissue repair have not been well characterized. Here, we employed translating ribosome affinity purification (TRAP) and RNA sequencing, TRAP-seq, in larval zebrafish to identify genes differentially expressed in neutrophils, macrophages, and epithelial cells in response to wounding. We ident… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 70 publications
0
28
0
Order By: Relevance
“…Previous studies in zebrafish have reported the use of TRAP methods for translational profiling in zebrafish using a few tissue-specific promoters 14,15,16,17 . Here we applied the Trap-TRAP strategy to generate random insertions of the eGFP-rpl10a cassette into the genome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in zebrafish have reported the use of TRAP methods for translational profiling in zebrafish using a few tissue-specific promoters 14,15,16,17 . Here we applied the Trap-TRAP strategy to generate random insertions of the eGFP-rpl10a cassette into the genome.…”
Section: Discussionmentioning
confidence: 99%
“…In zebrafish, different laboratories have successfully implemented the TRAP approach using tissuespecific drivers. They include the promoters of the genes tyrp1 for melanocytes 14 , cmlc2 for cardiomyocytes 15 , actc1b for skeletal myocytes 16 , or lyz for neutrophils 17 . One of the main disadvantages of the TRAP methodology is precisely the need to create a customized transgenic line for each cell type to be analysed.…”
Section: Introductionmentioning
confidence: 99%
“…The recruitment of neutrophils at the site of infection has also been observed ( Diaz-Pascual et al., 2017 ; McCarthy et al., 2017 ). The effect of neutrophil depletion in the outcome of P. aeruginosa in zebrafish embryos has not been investigated, but defects in neutrophil migration greatly sensitize embryos to P. aeruginosa infections ( Rosowski et al., 2016 ; Houseright et al., 2020 ). More precisely, embryos defective for Rac2 function, which have neutrophils that are unable to migrate, are highly susceptible to P. aeruginosa ( Rosowski et al., 2016 ).…”
Section: Interplay Of Pseudomonas Aeruginosa With the Zebrafish Innate Immune Systemmentioning
confidence: 99%
“…Upon localized otic infection with P. aeruginosa , systemic activation and mobilization of neutrophils from hematopoietic tissues is also mediated by Cxcr2 signaling, a receptor enabling neutrophils to sense the IL8 chemokine ( Deng et al., 2013 ). In addition, the increased susceptibility to P. aeruginosa infection observed in zebrafish deficient for c3a.1 , which is homologous to the C3 component of human complement, is likely due to a neutrophil-intrinsic function of C3, possibly its ability to recruit neutrophils at the infection site ( Houseright et al., 2020 ).…”
Section: Interplay Of Pseudomonas Aeruginosa With the Zebrafish Innate Immune Systemmentioning
confidence: 99%
“…Moreover, the expression of Myd88 and Tlr2 is significantly increased in diabetic wounded mice ( Dasu et al, 2010 ). In addition, some evidence indicate that Myd88 is involved in the modulation of wound healing ( Macedo et al, 2007 ; Houseright et al, 2020 ), but the underlying mechanism is still unclear. Although TLR signaling is important for chemokine production, little is known about the role of MyD88 in leukocyte migratory responses to tissue injuries in the absence of pathogenic infections.…”
Section: Introductionmentioning
confidence: 99%